Environmental Ethics of Kaki Air Village Community at Teluk Kaiely District Buru Regency - Fatimah Fatimah; Susiati Susiati; Noch Fernando Jelira; Chairul Basrun Umanailo; Saidna Zulfikar Bin Tahir (Hasanuddin University, 2021)
The purpose of this research is to 1) identify the community's ethical principles and 2) identify the variables that contribute to the establishment of community environmental ethics in Kaki Air Village. This study employs a qualitative descriptive method with a phenomenological orientation. The statistics were compiled through primary and secondary sources, with the major source being the residents of Kaki Air VillageThis study included non-participatory observation and field survey techniques (field study), as well as interviews (interviews), documentation studies, and literature research.. The data analysis step entails the reduction of data, its display, verification, and analysis. The study's findings indicate that the residents of Kaki Air Village have a particular brand of environmental ethics, namely that 1) humans are a part of nature. The visible qualities are divine values in this type of ethics; 2) nature is not to be dominated. This ethics upholds the virtue of politeness; 3) Support of other animals' rights to life. Concerning the ideals engendered by this ethics, namely the value of oneness; 4) exposing flaws in the maintenance system. This ethic is based on human and cultural values; 5) nature must be conserved. The ideals included in this ethics, particularly the value of wisdom and traditional values; 6) environmental stewardship. The principles created by this ethics are those of care and wisdom; 7) respect for the environment. The values produced by this ethic are those of concern and traditional values. The following elements contribute to the development of environmental ethical principles in the Kaki Air Village community: 1) attitude of the public; 2) natural environment; 3) regulation; 4) customs; 5) traditions; 6) sasi (Customary Law); 7) mata kao; 8) belief in the sacred; 9) belief in the landlord.